2014
DOI: 10.1002/2014jd021847
|View full text |Cite
|
Sign up to set email alerts
|

Mount Logan ice core record of tropical and solar influences on Aleutian Low variability: 500–1998 A.D.

Abstract: Continuous, high-resolution paleoclimate records from the North Pacific region spanning the past 1500 years are rare; and the behavior of the Aleutian Low (ALow) pressure center, the dominant climatological feature in the Gulf of Alaska, remains poorly constrained. Here we present a continuous, 1500 year long, calibrated proxy record for the strength of the wintertime (December-March) ALow from the Mount Logan summit (PR Col; 5200 m asl) ice core soluble sodium time series. We show that ice core sodium concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 118 publications
5
69
0
1
Order By: Relevance
“…Such large-scale changes in North Pacific pressure patterns have led to significant recent changes in hydroclimatic variables all along the west coast of North America (Belmecheri et al 2016;Diaz and Wahl 2015;Griffin and Anchukaitis 2014). A study by Moore et al (2004) also compares favorably with our results, indicating a long-term increase in snow accumulation at Mount Logan, British Columbia, in western Canada, as does that of Osterberg et al (2014), also using a Mount Logan ice core profile, both of whom found a strong association between snow accumulation and the strength of the Gulf of Alaska low pressure system.…”
Section: Summary and Discussionsupporting
confidence: 77%
“…Such large-scale changes in North Pacific pressure patterns have led to significant recent changes in hydroclimatic variables all along the west coast of North America (Belmecheri et al 2016;Diaz and Wahl 2015;Griffin and Anchukaitis 2014). A study by Moore et al (2004) also compares favorably with our results, indicating a long-term increase in snow accumulation at Mount Logan, British Columbia, in western Canada, as does that of Osterberg et al (2014), also using a Mount Logan ice core profile, both of whom found a strong association between snow accumulation and the strength of the Gulf of Alaska low pressure system.…”
Section: Summary and Discussionsupporting
confidence: 77%
“…A number of proxy records from the Bering Sea and adjacent regions, both marine and terrestrial, have been used to characterize paleoclimatic conditions related to changes in the Bering Sea pressure system (e.g., Barron et al, 2003;Anderson et al, 2005;Katsuki et al, 2009;Barron and Anderson, 2011;Osterberg et al, 2014). Various proxies used in these records consistently show that the Aleutian Low was overall weaker in the middle Holocene than in the late Holocene, the opposite of the BSI strength inferred from our Chukchi Sea data (Fig.…”
Section: Causes Of Bsi Variationsmentioning
confidence: 58%
“…The considerable climate variability in the Bering Sea region captured in the upper Holocene records, some of which have a very high temporal resolution, is also closely linked to the pressure system changes (Anderson et al, 2005;Porter, 2013;Osterberg et al, 2014;Steinman et al, 2014). In particular, the weakening of the Aleutian Low is reflected in Alaskan ice (Porter, 2013;Osterberg et al, 2014) and lake cores (Anderson et al, 2005;Steinman et al, 2014) at intervals centered around ca. 2 and 1-0.5 ka, which may correspond to BSI increases in the Chukchi core 01A-GC at ca.…”
Section: Causes Of Bsi Variationsmentioning
confidence: 98%
“…High-salinity snow blowing from the sea-ice surface has also been implicated as a significant source of polar sea-salt aerosol (Yang and others, 2008;Levine and others, 2014), which would likewise create a positive correlation between 2Barrel sea-salt and sea-ice concentration. The bursting of white cap bubbles on the open ocean, in proportion to average wind speeds, has also been interpreted as a key seasalt source at other ice-core sites (Fischer and others, 2007;Osterberg and others, 2014), but would likely result in a negative correlation with sea-ice concentration. It is likely that all these sources contribute in some proportion to 2Barrel sea-salt flux, and consequently sea salt is not as sensitive a sea-ice proxy as MSA or d-excess at the 2Barrel site.…”
Section: Msa-climate Relationshipsmentioning
confidence: 99%